Midwifery care in The Gambia: A focus group study with clinical midwives, midwifery students, educators and leaders on how barriers and facilitators impact quality midwifery care. - Lamin Suwareh; Helena Lindgren; Kerstin Erlandsson; Haddy Tunkara Bah; Evelina Holm; Majda Meljoum; Omar Manjang; Saineh Sanneh; Baboucarr Cham; Ulrika Byrskog (PLoS ONE)
Objective The aim of this study is to explore the impact of barriers and facilitators on the quality of midwifery care in The Gambia, from the perspectives of clinical midwives, midwifery students, educators, and leaders. Methods A qualitative study based on focus group discussions with 29 clinical midwives, midwifery students, educators and leaders analysed with content analysis. The study was conducted in The Gambia. Results The analyses led to three main categories outlining barriers and facilitators for the quality of midwifery care: 1) the gap between theory and practice, 2) working in a harsh environment and 3) facilitating factors that can pave ways forward. The results are described in generic categories: 1a) national plans and facility-based guidelines, 1b) midwifery education, 1c) becoming a skilled midwife, 2a) scarcity of resources, 2b) encountering community barriers, 2c) midwives - a passionate but demotivated profession, 3a) positive assets for quality midwifery care, 3b) women in leadership as a tool for a motivated midwifery workforce and 3c) teamwork. Conclusions Addressing the gaps between theory and practice, and strengthening the incentives for midwives to remain in their profession are central for improved quality of midwifery care in The Gambia. Guaranteed employment after completing education, equal opportunities for men and women to become midwives and the significance of passion are assets which need to be carefully maintained within the health care system.